Investigation of cationic contrast-enhanced computed tomography for the evaluation of equine articular cartilage - Nelson, Bradley B., author; Kawcak, Christopher E., advisor; Goodrich, Laurie R., advisor; McIlwraith, C. Wayne, committee member; Grinstaff, Mark W., committee member; Barrett, Myra F., committee member (Colorado State University. Libraries, 2017)
Osteoarthritis and articular cartilage injury are substantial problems in horses causing joint pain, lameness and decreased athleticism resonant of the afflictions that occur in humans. This debilitating joint disease causes progressive articular cartilage degeneration and coupled with a poor capacity to heal necessitates that articular cartilage injury is detected early before irreparable damage ensues. The use of diagnostic imaging is critical to identify and characterize articular cartilage injury, though currently available methods are unable to identify these early degenerative changes. Cationic contrast-enhanced computed tomography (CECT) uses a cationic contrast media (CA4+) to detect the early molecular changes that occur in the extracellular matrix. Glycosaminoglycans (GAGs) within the extracellular matrix are important for the providing the compressive stiffness of articular cartilage and their degradation is an early event in the development of osteoarthritis. Cationic CECT imaging capitalizes on the electrostatic attraction between CA4+ and GAGs; exposing the proportional relationship between the amount of GAGs present within and the amount of CA4+ that diffuses into the tissue. The amount of CA4+ that resides in the tissue is then quantified through CECT imaging and estimates tissue integrity through nondestructive assessment. Despite the emergence of this promising technology to capture quantitative information on articular cartilage quality, cationic CECT has not been thoroughly investigated in equine tissues in vitro or in vivo, nor has it been investigated in in vivo in any large animal or human subjects. This compilation of studies was designed to critically examine the capacity of cationic CECT to provide quantitative information on articular cartilage quality across a continuum of disease states in horses while dually serving as a translational model to showcase its potential application in humans. The first experiments successfully characterized the diffusion properties of CA4+ into equine articular cartilage in vitro and in vivo, and also established the femoropatellar joint as the optimum joint for use in the subsequent in vivo experimental models. These initial studies also established preliminary evidence of the safety of CA4+ on articular tissues. The experimental in vivo equine impact model delivered a contusive force to articular cartilage that successfully instituted degeneration of the extracellular matrix components and decreased tissue stiffness. This subtle degradation was discernable from healthy articular cartilage using cationic CECT imaging (microCT). In vivo, the clinical cationic CECT attenuation demonstrated fair correlations with the biochemical, mechanical and histologic staining measures, though there was not sufficient delineation among groups to detect significant differences between disease states. Further investigations are warranted to determine how focal sites of injury can be identified from the resolution limited by current CT technology. The second in vivo experimental study generated reparative and degenerative articular cartilage to provide comparisons with healthy tissue. The cationic CECT method, using microCT and clinical scanners, demonstrated an ability to distinguish between these groups of varying articular cartilage quality. Though the results were promising, this study revealed the complexity of detecting subtle articular cartilage injury in a solitary imaging examination owing to the inherent biochemical and biomechanical variation that exists across articular surfaces. However, this study confirmed the successful monitoring of articular cartilage through longitudinal examinations. Overall, this collection of studies established that cationic CECT imaging in vitro and in vivo is capable of distinguishing articular cartilage across a spectrum of disease states exemplifying its utility in the comprehensive evaluation of equine articular cartilage. Further work of how this technique compares to other quantitative diagnostic imaging techniques and optimization strategies for routine use are required. Nonetheless, the results of this work reveal the excellent potential of cationic CECT imaging to be incorporated into research and clinical investigations in horses and highlight the feasible translation of this work into human tissues.
Keywords: glycosaminoglycan; imaging; osteoarthritis; horse; contrast media; orthopedic